Opportunities and barriers to translating the hibernation phenotype for neurocritical care - Drew, Kelly L.; Bhowmick, Saurav; Laughlin, Bernard W.; Goropashnaya, Anna V.; Tøien, Øivind; Sugiura, M. Hoshi; Wong, Ardy; Pourrezaei, Kambiz; Barati, Zeinab; Chen, Chao-Yin (Frontiers in Neurology, 2023)
Targeted temperature management (TTM) is standard of care for neonatal hypoxic ischemic encephalopathy (HIE). Prevention of fever, not excluding cooling core body temperature to 33°C, is standard of care for brain injury post cardiac arrest. Although TTM is beneficial, HIE and cardiac arrest still carry significant risk of death and severe disability. Mammalian hibernation is a gold standard of neuroprotective metabolic suppression, that if better understood might make TTM more accessible, improve efficacy of TTM and identify adjunctive therapies to protect and regenerate neurons after hypoxic ischemia brain injury. Hibernating species tolerate cerebral ischemia/reperfusion better than humans and better than other models of cerebral ischemia tolerance. Such tolerance limits risk of transitions into and out of hibernation torpor and suggests that a barrier to translate hibernation torpor may be human vulnerability to these transitions. At the same time, understanding how hibernating mammals protect their brains is an opportunity to identify adjunctive therapies for TTM. Here we summarize what is known about the hemodynamics of hibernation and how the hibernating brain resists injury to identify opportunities to translate these mechanisms for neurocritical care.